Anti-CD73 immunotherapy: A viable way to reprogram the tumor microenvironment. (1st September 2016) - Antonioli, Luca; Blandizzi, Corrado; Malavasi, Fabio; Ferrari, Davide; Haskó, György
Abstract: The ecto-5'-nucleotidase/CD73 enzyme plays a pivotal role in generating an adenosine-enriched immunosuppressed and pro-angiogenic niche supporting cancer development. The targeting of CD73 leads to reorganization of tumor microenvironment, shaping the phenotype of the infiltrating T cells. The development of CD73 monoclonal antibodies offers a promising new avenue for antineoplastic treatment.